‘Slow libraries’ and ‘Cultural AI': - Vicky Breemen; Kelly Breemen (Technology and Regulation, 2025)
Cultural heritage institutions (galleries, libraries, archives, and museums; CHIs or GLAM) increasingly experiment with the use of artificial intelligence (AI) in epistemological tools for unlocking their collections. The use of AI poses both opportunities and risks, a notable risk being bias and silencing non-dominant perspectives. It is therefore time to rethink the design and regulation of AI. With the input of histories of, and developments in, collecting and unlocking cultural heritage, and various theories on cultural AI, regulation by design, and value alignment, this paper applies a law & humanities perspective to examine ‘cultural AI’ and ‘slow archives’ approaches in view of our envisaged output: the contours of a conceptual framework for the value-based regulation by design of culturally sensitive, fair and insightful AI in GLAM practice.